PENGARUH KOMPETENSI TERHADAP KINERJAPEGAWAI PADA PUSKESMAS KECAMATAN DARUSSALAM KABUPATEN ACEH BESAR - Syamsul Akmal (Jurnal Sosial Humaniora Sigli, 2020)
This study aims to determine "The Influence of Competence on Employee Performance at Puskesmas Darussalam District, Aceh Besar District". Where the independent variables are Knowledge (X1), Skills (X2), Behavior (X3) and Work Experience (X4) and Employee Performance (Y) as the dependent variable. Population in this research is employee Puskesman District Darussalam. Samples were taken as many as 97 samples using saturated sampling technique (census). Data were collected using questionnaires filled out by respondents. The data obtained were analyzed by multiple linear regression. This analysis includes Test Validity, Reliability Test, Multiple Regression Analysis Test Classic Assumption, Hypothesis Testing through F Test and t Test , and Determination Coefficient analysis (R2). Based on the results of the study, obtained Y = 1.581 + 0.268 X1 + 0.232 X2 + 0.232 X3 + 0.430 X4. Of the four variables studied, only the working experience variables (X4) has the most dominant effect of 0.430 to the Performance of employees at the Puskesmas Darussalam District, Aceh Besar District. The relationship of each Knowledge (X1), Skill (X2), Behavior (X3) and Work experience (X4) to the Performance of employees at Puskesmas Darussalam District, Aceh Besar Regency with correlation coefficient (R) of 0.961 means that the relationship is very strong. Fcount> Ftable at 95% confidence level (a = 0.05), that is 175.092> 2.47. Then the coefficient of determination of each variable Knowledge (X1), Skills (X2), Behavior (X3) and Work Experience (X4) of 0.924 or 92.4% to Employee Performance (Y) means the four variables simultaneously affect Employee Performance on Puskesmas Darussalam District, Aceh Besar District, only 7,6% influenced by other variable not examined in this research. Keywords: Knowledge, Skills, Behavior, Work Experience and Performance